Factors Influencing the Utilization of Childbirth Services in Health Care Facilities at UPTD Anggaberi Health Service Center, Konawe District - Murti Wuryani; Arni Evayanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
The childbirth coverage in health facilities (PF) at UPTD Anggaberi Public Health Center  in 2017 has reached 72.6%, and increased in 2018 by 76.18%. At district level, the PF indicator at UPTD Anggaberi Public Health Center  has exceeded the target in Konawe District by 59,37%, however but the 80% target achievement of PF at the UPTD Anggaberi Public Health Center  has not been achieved6. Seeing this, the coverage of PF at the UPTD Anggaberi Public Health Center , there are still labors that are not performed in health facilities, so that it can affect the achievement of PF at the UPTD Anggaberi Public Health Center , Konawe District. The aim of the study was to analyze factors that influence utilization of health care facilities at the UPTD Anggaberi Public Health Center. This research is an analytical study with a cross sectional approach. The research instrument used was a structured questionnaire on the factors that affect the utilization of labor service in health care facilities. The number of samples was 51 women who had labor at the Anggaberi Health Center. Bivariate analysis was done with chi square test and multivariate analysis with logistic regression test. The results showed the six factors (education (p = 0.041) and work (p = 0.019) family income (p = 0.041) and accessibility (p = 0.021) husband support (p = 0.011) and health personnel support (p = 0.011) ) on the use of childbirth services in health care facilities at the UPTD Anggaberi Public Health Center , Konawe District. The multivariate results show that all independent variables in this study have a significance limit of p-value ≤ 0.25, so it can be concluded that there is an influence among each independent variable (education, occupation, income, accessibility, husband's support and support of health workers) with the dependent variable. (utilization of childbirth services in health service facilities). Health care centers are expected to improve the partnership with traditional midwife (dukun beranak) within their work area so that the dukun can become well trained and they can collaborate in every childbirth